Challenges in English Language Learning at SMP Muhammadiyah Piyungan: A Case Study - Konipa, Monica Gita; Pratolo, Bambang Widi; Nguyen, Tran Thi Hoang (Ahmad Dahlan Journal of English Studies, 2025)
This study explores the challenges faced in teaching English at SMP Muhammadiyah Piyungan, focusing on variations in student proficiency, motivational issues, technological constraints, assessment difficulties, and classroom management. Using qualitative research methods, including classroom observations, semi-structured interviews with teachers, and student surveys, the study identifies strategies to address these challenges. Findings reveal that differentiated instruction and interactive teaching methods enhance student engagement and motivation. However, issues such as limited access to technology and inadequate assessment methods persist. The study emphasizes the importance of collaboration among teachers, parents, and administrators to create a supportive learning environment. Recommendations include professional development for teachers and the integration of culturally responsive teaching practices to improve English language education at the junior secondary level.